TLC-Based Fingerprinting Analysis of the Geographical Variation of Melastoma malabathricum in Inland and Archipelago Regions: A Rapid and Easy-to-Use Tool for Field Metabolomics Studies - Mayasari, Dian (American Chemical Society, 2022)
Melastoma malabathricum is an Indo-Pacific herb that has been used traditionally to treat numerous ailments such as wounds, dysentery, diarrhea, toothache, and diabetes. The objective of this study was to evaluate the variability of the metabolic profiles of M. malabathricum across its geographic distribution. By employing thin layer chromatography (TLC), specimens collected from six terrestrial and archipelago regions of Indonesia were analyzed by densitometry for metabolomic fingerprinting analysis combined with chemometric tools: principal component analysis (PCA) and hierarchical cluster analysis (HCA). Two PCAs were identified as PC1 and PC2 with 41.90 and 20.36, respectively. Our results indicate the importance of considering geographic distribution during field-collection efforts since they demonstrate regional metabolic variation in secondary metabolites of M. malabathricum, as illustrated by TLC and their biological activities. © 2021 American Chemical Society and American Society of Pharmacognosy